A hybrid control strategy to control active filter and improve the PQ of non-linear load. Issue 1 (2nd January 2016) - Sahithullah, M.; Senthil Kumar, A.
Abstract: Nowadays, the power quality (PQ)-related issues are more absorbed in power electronic devices. For compensating PQ disturbances, various types of power devices are used. The shunt active power filter (SAPF) is one of the power electronics devices that are used for enhancing the PQ. To reduce the PQ disturbances, the performance of SAPF must be improved. In this paper, a hybrid controller is proposed for improving the performance of SAPF and compensating the PQ. The hybrid technique is the combination of cuckoo search algorithm and radial basis function neural network technique which is used for extracting the reference current for compensating the SAPF and reducing the PQ problem. The SAPF is used for reducing the harmonic disturbances. The DC-link voltage is regulated by utilizing the proposed hybrid controller technique. Subsequently, the Fast Fourier Transform analysis is used for measuring total harmonic distortion values of the proposed system. The proposed method is implemented in MATLAB/Simulink platform and its performance is evaluated. The performance of the proposed method is evaluated and compared with the proportional–integral controller and fuzzy controller.